2010
DOI: 10.1890/08-2131.1
|View full text |Cite
|
Sign up to set email alerts
|

Marine reserves: Fish life history and ecological traits matter

Abstract: Abstract. Marine reserves are assumed to protect a wide range of species from deleterious effects stemming from exploitation. However, some species, due to their ecological characteristics, may not respond positively to protection. Very little is known about the effects of life history and ecological traits (e.g., mobility, growth, and habitat) on responses of fish species to marine reserves. Using 40 data sets from 12 European marine reserves, we show that there is significant variation in the response of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
228
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(247 citation statements)
references
References 57 publications
13
228
3
Order By: Relevance
“…Demonstrating the effectiveness of spatial closures for protecting wide-ranging, migratory species (e.g. the large coastal/semi-pelagics and hammerheads) is challenging, although evidence suggests that these species may receive some benefits from spatial closures (Claudet et al 2010). Many of the patterns observed in this study (e.g.…”
Section: Risk Mitigation Strategies In Multispecies Tropical Shark Fmentioning
confidence: 83%
“…Demonstrating the effectiveness of spatial closures for protecting wide-ranging, migratory species (e.g. the large coastal/semi-pelagics and hammerheads) is challenging, although evidence suggests that these species may receive some benefits from spatial closures (Claudet et al 2010). Many of the patterns observed in this study (e.g.…”
Section: Risk Mitigation Strategies In Multispecies Tropical Shark Fmentioning
confidence: 83%
“…In addition, studies within taxonomic groups should examine whether alien species of similar traits have similar responses to protection. Functional traits have been associated with the invasiveness of alien marine species (e.g., Elleouet et al, 2014;Samaha et al, 2016) as well as to the response of native species to protection (e.g., Claudet et al, 2010). Hence, alien/invasive species of similar traits are likely to display similar patterns and tendencies within MPAs.…”
Section: Discussionmentioning
confidence: 99%
“…Though MPAs are primarily considered a conservation tool, with eventual economic interest based on tourist activity, there is evidence that MPAs can also be used as a fisheries management tool, as benefits for local fisheries have been observed (Russ et al 2004;McClanahan et al 2006), although these benefits depend on a number of factors a Corresponding author: timothee.brochier@gmail.com (White et al 2010). It has been shown that the spill-over of an MPA, i.e., the number of fish "exported" from the MPA that become available for fishing, is related to a number of parameters including pre-and post-reserve human exploitation level, MPA size, shape, age, fish life history and fish ecological traits (Claudet et al , 2010White et al 2010). This has motivated considerable research toward the development of scientific tools that aid in decision making for MPA design (Pelletier et al 2008;Kaplan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Living Resour. 26, 147-158 (2013) migrations have been demonstrated to determine the impact of MPAs on species but are not sufficiently taken into account in MPA studies (Claudet et al 2010;Grüss et al 2011). This is a direct consequence of the use of classical methodological approaches, such as MARXAN (Ball et al 2009) or ECOPATH (Christensen et al 2005(Christensen et al , 2009, which generally examine the system in a static state without considering species interactions or migrations.…”
Section: Introductionmentioning
confidence: 99%